2019
DOI: 10.1590/s1677-5538.ibju.2018.0521
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience of video endoscopic inguinal Lymphadenectomy in a center located at northeast brazilian region

Abstract: Introduction: Video endoscopic inguinal lymphadenectomy – VEIL – has emerged as an alternative to reduce post-surgical complications (PSC) in patients with penile cancer submitted to inguinal lymphadenectomy (IL). In some series, these PSC are observed in more than 50% of patients. The objectives of the present study are to describe the initial experience of VEIL in a Hospital in Teresina, PI, Brazil, and to analyze PSC incidence. Material and Methods: Retrospective des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…After that, several other series and three systematic reviews with pure laparoscopic or robotic techniques have reported further evidence supporting the findings from that landmark comparative study (18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 57%
“…After that, several other series and three systematic reviews with pure laparoscopic or robotic techniques have reported further evidence supporting the findings from that landmark comparative study (18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 57%
“…Meneses et al . [ 30 ] followed up 11 patients for a mean period of 28 months and 2 patients had recurrence. Carlos et al .…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple interventions to try to fulfill this objective, such as topic chemotherapy with imiquimod and 5-fluorouracil, laser with carbon dioxide or neodymium: yttrium-aluminum-garnet (Nd: YAG), glans resurfacing excision with circumcision laser, glansectomy with reconstruction, radiotherapy, partial amputation with reconstruction, radical penectomy with perineal urethrostomy, neoadjuvant or adjuvant therapy with surgery, among other interventions (14,15). Also, there are different interventions for managing the inguinal region with the potential to limit morbidities, such as the dynamic sentinel node excision and the video endoscopic inguinal lym-ph node dissection (VEIL) (16,17). T1 low-grade patients could be treated with a conservative approach; otherwise, higher T or high-grade stages will require more extensive procedures (1, 2, 18).…”
Section: Commentmentioning
confidence: 99%